Toward a Gender-Sensitive Securitization of the Common European Asylum System - Le Bellec, Amandine (Frontiers in Human Dynamics, 2021)
EU Member States may legally designate a country as a Safe Country of Origin when human rights and democratic standards are generally respected. For nationals of these countries, asylum claims are treated in an accelerated way, the underlying objective of the “safe country” designation being to facilitate the rapid return of unsuccessful claimants to their country of origin. The concept of “safe country” was initially blind to gender-based violence. Yet, in the reform of the Common European Asylum System (CEAS), which began in 2016, the European Commission proposed two changes: first, that a common list of “safe countries” should be applied in all Member States, and second, that this concept should be interpreted in a “gender-sensitive” manner. In consequence, the generalization of a policy that has been documented as largely detrimental to asylum seekers has been accompanied by the development of special guarantees for LGBTI+ asylum seekers. In light of this, there is a need to examine the impact of “safe country” practices on LGBTI+ claimants and to investigate the extent to which the securitization of European borders is compatible with LGBTI+ inclusion. Based on a qualitative document analysis of EU “safe country” policies and on interviews with organizations supporting LGBTI+ asylum seekers, this article shows that despite the implementation of gender-sensitive safeguards, LGBTI+ asylum seekers are particularly affected by “safe country” practices. These practices permeate European asylum systems beyond the application of official lists, depriving many LGBTI+ asylum seekers of their right to have their protection claims fairly assessed.